(untitled) (TEST Ticontre. Theory Text Translation, 2022)
Within the frame of Posthuman Studies, blue humanities emphasize the role of under-water perspectives in literary criticism. Here the strategy is applied to different poems by Jorie Graham, Laura Accerboni and Marwa Helal, in order to establish the sea as a major allegory of the Digital Era in terms of hardware, network and user-generated content.